An Efficient E-Wallet Mechanism Protecting Privacy, Security and Unobservability - Edith Linda, P; Anand, S. Vijay; Srividhya, R (International Journal of Computer Sciences and Engineering, 2019)
Contactless payment systems are one which uses credit and debit cards, key fob, smartcards and other mobile devices that use radio frequency identification or other types to make the payments a secured one. It is not the one which involves close physical proximity. It involves wifi networks or broad area cellular network to perform the transaction. In this paper we present a exploration on the selected terminology of contactless payments, its genealogy, the securities involved on contactless payments. The present study relates generally to transaction processing techniques and associates systems. The paper contributes to study of the various digital payment mechanisms and their transparency in doing the financial transactions. The study relates to methods and systems for monitoring immediacy contactless payment transactions and assisting consumers with use of their payment gateways in carrying out the proximity contactless payment transactions.